"Do Not Fear Mistakes—There Are None": Ethnography as Improvisation. Issue 1 (24th December 2021) - METZO, KATHERINE
Abstract : I use the iconic album, Kind of Blue, to re‐frame a conversation around ethnography and innovation. Moving fast and breaking stuff is not how ethnography brings value to the business. Rather, we use our craft to move nimbly through the complex terrain of "users" in much the same way as jazz musicians improvise. We are grounded in our craft through practice, but technical mastery is not enough. Bounded by structures and constraints, we move nimbly because knowing the rules allows us to creatively push against boundaries. And ethnography never exists in a vacuum, even if we're the only anthropologist in the room. Instead, we riff off those who came before us, in community with those who innovate alongside us. The core value of ethnography is to improvise—to use our mastery of our craft to build on what came before, to make sense of it, and anticipate what comes next.